Viscum album L. mother tinctures modulate Na+/K+ ATPase activity and expression, and promote endothelium-dependent vasodilation via SK channel and nitric oxide signalling - Duarte, Rodrigo dos Santos Pinto; Melo, Michelle Nonato de Oliveira; Batista, João V. C.; Martins, Giovanna Gomes; Oliveira, Adriana Passos; Taveira-da-Silva, Rosilane; da Silva, Maria Luiza Fidelis; Valverde, Rafael H. F.; Einicker-Lamas, Marcelo; Gasparotto Junior, Arquimedes; Baumgartner, Stephan; Holandino, Carla (Frontiers in Physiology, 2026)
IntroductionEthanolic extracts of Viscum album L. (European mistletoe), known as mother tinctures (VAMTs), have been used in traditional medicine to treat hypertension and cardiovascular diseases. However, the underlying biological mechanisms remain poorly characterized. MethodsThis study investigated the cytotoxic, and cardiovascular effects of ten VAMTs prepared from fresh plants harvested in summer and winter. The extracts were derived from three subspecies (V. album subsp. album, abietis, and austriacum) growing five distinct host tree species. Cytotoxicity and oxidative stress were assessed in vitro, while the effects on Na+/K+-ATPase activity and expression were evaluated in porcine renal proximal tubular cells. Additionally, vascular effects were investigated in perfused mesenteric vascular beds of spontaneously hypertensive rats. Results and DiscussionOur data demonstrated that VAMTs exhibit no cytotoxic effects, except for the VAMT derived from Quercus petraea, and do not induce oxidative stress in in vitro assays. Regarding molecular targets, distinct profiles were observed: the VAMT derived from A. alba (summer harvest) reduced Na+/K+- ATPase expression and activity in the cellular model, whereas all winter VAMTs reduced only the expression of this enzyme. The winter VAMT from P. sylvestris (VAMT PW) elicited vasodilation in resistance arteries from hypertensive rats. This vasodilatory effect appears to be mediated by the nitric oxide/soluble guanylate cyclase/cyclic guanosine monophosphate signalling pathway and the subsequent activation of small conductance calcium-activated potassium channels. These data support the efficacy of VAMT PW and emphasise the impact of the host tree and season for optimizing antihypertensive potential of V. album samples in the context of traditional mistletoe medicine.